Crickets with phallic glands: two new genera and one new species of Brazilian Luzarinae (Grylloidea: Phalangopsidae) - Mews, Carina Marciela; Mól, Abel Perigolo; Sperber, Carlos Frankl (Zootaxa, 2009)
Phalangopsidae is the cricket’s family with highest species diversity in the Brazil. The aim of this study was to describe one new species of Izecksohniella, and two new Brazilian unspecific genera related to it. Marliella titai gen. nov. et sp. nov. and Joadis mesai gen. nov. et sp. nov. were characterized by genitalia morphology, reduced wings, presence of metanotal and phallic glands.